Daily-Mean-SOFA, a New Derivative to Increase Accuracy of Mortality Prediction in Cardiac Surgical Intensive Care Units - Badreldin, Akmal; Elsobky, Sherif; Lehmann, Thomas; Brehm, Bernhard B.; Doenst, Torsten; Hekmat, Khosro (The Thoracic and Cardiovascular Surgeon, 2012)
Background Sequential organ failure assessment (SOFA) score is widely used in many cardiac surgical intensive care units (ICUs). Its derivatives (mean and maximum values) are known to be more accurate than the original daily values of SOFA itself. However, they were designed for research purposes and could be calculated only after ICU discharge. We aimed to develop a reliable derivative that can be easily calculated daily (Daily-Mean-SOFA) for aiding daily-decision-making and resource allocation.Methods All consecutive adult cardiac surgical patients from our ICU between January 1, 2007 and December 31, 2008 were included. We obtained Initial-SOFA (on day 1), the Original-Daily-SOFA value from the 1st to the 6th postoperative day, Max-SOFA (highest SOFA value during the whole ICU-stay), Mean-SOFA (sum of all daily SOFA values/the length of ICU-stay), and the new “Daily-Mean-SOFA” from day 2 to 6 (sum of SOFA from day 1 until day-n/n). We compared their accuracies at predicting ICU mortality using calibration and discrimination statistics.Results Total 2801 patients were included. The newly developed “Daily-Mean-SOFA” was significantly more accurate than the corresponding SOFA value of the same day in correctly predicting survival and mortality in the whole study population (OCC: 94.1 to 95.0%) and in accurately identifying the individual patient’s risk of mortality (AUC: 0.859 to 0.904). It was better than all other derivatives except the Mean-SOFA which was superior to it (OCC: 96.3%; AUC: 0.913).Conclusions The Daily-Mean-SOFA is a reliable derivative for daily risk stratification in cardiac ICUs. Due to its accuracy and daily availability, it may be used for risk-directed therapy in cardiac ICUs.
Keywords: outcomes (includes mortality morbidity); intensive care; statistics